2016
DOI: 10.5430/jnep.v7n5p62
|View full text |Cite
|
Sign up to set email alerts
|

Determination nurses’ knowledge about initial drugs used during emergency management of acute myocardial infarction

Abstract: Objective: Acute myocardial infarction is a life threatening condition that influences the physical, psychological and social dimensions of the individual. The aim of this study was conducted to determine nurses’ knowledge of initial treatment during an emergency management of patients with acute myocardial infarction.Methods: A descriptive study was used. The standardized administered questionnaires were administered on 139 critical care nurses who are employed in five teaching hospitals at Khartoum state/Sud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…The preference for higher education over specialized training might be contributing to a gap in the availability of specialized nursing skills in critical areas like thrombolytic therapy. 4,5,17,18 The study highlighted significant findings regarding knowledge and task performance in thrombolytic therapy administration. The overall knowledge score was relatively high at 71%, but the task performance score was notably low at 49%.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The preference for higher education over specialized training might be contributing to a gap in the availability of specialized nursing skills in critical areas like thrombolytic therapy. 4,5,17,18 The study highlighted significant findings regarding knowledge and task performance in thrombolytic therapy administration. The overall knowledge score was relatively high at 71%, but the task performance score was notably low at 49%.…”
Section: Discussionmentioning
confidence: 91%
“…4,17,18 Similarly, a study in Sudan found a significant lack of knowledge regarding Streptokinase. 5 Conversely, studies in Palestine and South Africa reported good knowledge among nurses. 6,11 The differences in knowledge levels could be attributed to the varying emphasis on nursing responsibilities and continuous professional development in different healthcare systems.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cardiovascular diseases (CVDs) account for one in ve deaths in the united states and are the leading cause of mortality in most countries worldwide (1). Various risk factors such as age, male sex, race, unhealthy lifestyle, smoking, diabetes mellitus, hypertension, hyperlipidemia, and positive family history have been associated with CVDs (2). Notably, one of the most critical acute manifestations of CVDs is acute ST-elevation myocardial infarction (MI) which is caused by occlusion of coronary arteries due to the formation of a culprit clot leading to the sudden cessation of blood ow to the myocardium (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Nurses' conformance to treatment protocols and guidelines has led to a fall in the mortality and morbidity associated with CVD (2,(8)(9)(10). World Health Organization (WHO) and American Heart Association (AHA) have delineated the role of nurses in reducing CVD by 25% by the year 2025; therefore, nurses' knowledge should be updated regularly (11).…”
Section: Introductionmentioning
confidence: 99%